The quality of anti-corruption education in Indonesian schools: adaptation of the Servqual method - Santoso, Ridwan; Murdiono, Mukhamad; Muhson, Ali; Nadya, Lucky (International Journal of Evaluation and Research in Education (IJERE), 2024)
Anti-corruption education is a character education program that aims to instill anti-corruption values in students. The difference in the implementation of anti-corruption education as an autonomous subject provides different learning experiences for students. This research aims to measure the quality of anti-corruption education using the Servqual instrument. The Servqual instrument was developed and analyzed using confirmatory factor analysis (CFA). This research was conducted with an ex-post facto non-experimental design. The subjects involved were 156 students. Data analysis was carried out with the SmartPLS program. The results of CFA show that the instrument meets the fit criteria. Thus, the discriminant validity results have met the criteria, with a composite reliability (CR) value of 0.765 to 0.900. The results of the path analysis prove that three of the five Servqual constructs have a significant effect on the quality of anti-corruption education.